Hipnoterapy Toward Improving The Confidence Of Students - Sri Wahyuni Rifai; Asnidar; Edison Siringoringo (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2019)
The problem of confidence is one of the global phenomena that everyone has. This event does not only occur in Indonesia but also in other countries. From the results of preliminary studies conducted by researchers, more respondents experienced low self-esteem than moderate and high self-esteem. The purpose of this study was to determine the effect of hypnotherapy on increasing the confidence of students in the fourth semester of the S1 undergraduate study program in the learning process at Stikes Panrita Husada Bulukumba. This research method uses a Pre-experimental design with the One group Pretest-Posttest Design approach. Sampling was done by a systematic random sampling technique. The population in this study was 46 people. The sample in this study were 19 people. Data analysis uses the Marginal Homogeneity alt Wilcoxon test. The results of SPSS analysis using the statistical test Marginal Homogeneity alt Wilcoxon obtained the value (p = 0.001) so that it can be concluded that there is a significant influence between hypnotherapy on increasing the confidence of fourth-semester students of a nursing S1 study program in the learning process at Stikes Panrita Husada Bulukumba.